Preserving Sacred Space: Identity of the Chinese Temples in Thailand - Khemarin Pensaengon; Tawan Wannarat; Pipat Suya; Watcharin Anekpongpan (IAFOR Journal of Cultural Studies, 2025)
Chinese temples serve as enduring symbols of Chinese identity that have been faithfully passed down through generations of ancestors. In the lives of Chinese diaspora communities, the preservation of their identity is a fundamental element. The Chinese community has been settled in Thailand for more than two centuries. Many studies proposed that the Chinese were assimilated by the Thai, but this work found that there remains a strong identity through Chinese temples in Thailand. To understand the roles of these Chinese temples in preserving identity, the study embraces a qualitative case study methodology which includes document analysis, participant observation, and in-depth interview. This study explores how Chinese shrines sustain their identity through the community engagement in Nakhon Pathom Province, Thailand. The study also identifies the challenges that occur with Chinese temples trying to sustain a Chinese identity. The study found that Chinese temples in Thailand actively engage with the community in various ways, fostering a sense of belonging, cultural preservation, and community support. Chinese temples in Thailand also play a multifaceted role in the lives of the Thai Chinese community. They serve as religious centers, cultural hubs, educational institutions, and support networks, all of which contribute to the cultural vibrancy and cohesion of the community while also enriching the broader Thai cultural landscape. However, Chinese temples or shrines in Thailand face several challenges, some of which are unique to their cultural and religious context in the country.